Household "ethnoscapes" and rite of passage: meaning and chronicity of the diagnosis in schizophrenia - Alegre-Agís, Elisa (Revista de Antropología Social, 2016)
Based on the results of an ethnographic study with people diagnosed with schizophrenia and their relatives in Barcelona and Tarragona along one year, I problematize the transformation of roles and relationships inside the household from the first burst and the assignation of a diagnosis as rite of passage. I appeal to a cultural interpretation of family, understanding the family group as a specific ethnoscape. I analyze the chronicity meaning, and its consequences in the conformation of the “role of sick person” in the context of parental relationships. I also discuss the paradoxes in terms of autonomy for the affected persons because of the projection of cultural connotation of chronicity.
Keywords: schizophrenia; role; family; chronicity; rite of passage.